Identification of Annexin A4 as a hepatopancreas factor involved in liver cell survival - Zhang, Danhua (Dev Biol, 2014)
To gain insight into liver and pancreas development, we investigated the target of 2F11, a monoclonal antibody of unknown antigen, widely used in zebrafish studies for labeling hepatopancreatic ducts. Utilizing mass spectrometry and in vivo assays, we determined the molecular target of 2F11 to be Annexin A4 (Anxa4), a calcium binding protein. We further found that in both zebrafish and mouse endoderm, Anxa4 is broadly expressed in the developing liver and pancreas, and later becomes more restricted to the hepatopancreatic ducts and pancreatic islets, including the insulin producing β-cells. Although Anxa4 is a known target of several monogenic diabetes genes and its elevated expression is associated with chemoresistance in malignancy, its in vivo role is largely unexplored. Knockdown of Anxa4 in zebrafish leads to elevated expression of caspase 8 and Δ113p53, and liver bud specific activation of Caspase 3 and apoptosis. Mosaic knockdown reveal that Anxa4 is required cell-autonomously in the liver bud for cell survival. This finding is further corroborated with mosaic anxa4 knockout studies using the CRISPR/Cas9 system. Collectively, we identify Anxa4 as a new, evolutionarily conserved hepatopancreatic factor that is required in zebrafish for liver progenitor viability, through inhibition of the extrinsic apoptotic pathway. A role for Anxa4 in cell survival may have implications for the mechanism of diabetic β-cell apoptosis and cancer cell chemoresistance.